Analisa Pengaruh Sudut Stagger Di Depan Advancing Blade Terhadap Performa Turbin Air Savonius Myring Blade n=1 & n=2 - Alfin Ardianto; Priyo Agus Setiawan; Nopem Ariwiyono (Proceedings Conference on Marine Engineering and its Application, 2020)
Savonius water turbines can work at low fluid flow rates and have high torque, but have disadvantageswhich is the lowest Cp value compared to other turbine types. Efficiency can be improved by changing the shapeof the Savonius Turbine blade using the myring equation and adding an obstacle. The experimental method in thisstudy combines two blades resulting from variations of the value (n) in the myring equation n = 1 and n = 2, withmyring n = 1 placed on the concave side and n = 2 on the convex side. To improve performance, a 12 cm diametercircular cylinder is placed in front of the advancing blade with varying stagger angles. The test model has a heightof 0.40 m and a diameter of 0.40 m which will be tested in a flowing tank with a width of 1 m and height of 1 m.Experiments were carried out at a current speed of 0.2 m / s by measuring the turbine rotation and load to producea torque coefficient and a power coefficient. The experimental results show that the placement of the circularcylinder with ds / D = 0.3, S / D = 0.75, and ? = 60º obtained the highest performance with an angular velocityof 0.5160 rad / s, Coefficient of torque (Ct) of 0.2936 and Coefficient of power (Cp) of 0.1515. With a percentageincrease compared to myring n = 1 and n = 2 without an obstacle of 10.27%, this proves that the addition of acircular cylinder can improve the performance of Savonius water turbines.